Management Styles in Different Stages of Company´s Life Cycle with Empirical Example of Apple Corporation - Pleshakova, Elena; Pichanič, Mikuláš, 1942-; Staňková, Lenka; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
Since 19th century and great minds like Frederick Taylor or Henri Fayol, the theory of management went through consequential changes. Every new scholar was developing theories that in turn were raising new question and challenges for management. Until today, no single theory was globally recognized. Every modern management concept is arguing for the right to be the only correct, without giving a clear answer on how to manage the company and employees effectively. However, nowadays it is not enough to be a master in the field of finance, accounting, commerce or any other sciences to successfully manage the department or the company. Managing requires working with people, each of whom is endowed with a certain knowledge base, and more importantly with values, interests and work styles. The modern literature points to the need to choose the right style of management, however, a variety of information about the "ideal manager" often contradict one another.For the purpose of studying the methodology used is based on documentary analysis of most commonly used managerial styles presented by different management scholars. Different theories are connected and combined into consolidated model that is derived from both psychological aspects of human nature and the functions every manager should perform.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses